Time-resolved record of 236U and 239, 240Pu isotopes from a coral growing during the nuclear testing program at Enewetak Atoll (Marshall Islands). (December 2016) - Froehlich, M.B.; Chan, W.Y.; Tims, S.G.; Fallon, S.J.; Fifield, L.K.
Abstract: A comprehensive series of nuclear tests were carried out by the United States at Enewetak Atoll in the Marshall Islands, especially between 1952 and 1958. A Porites Lutea coral that was growing in the Enewetak lagoon within a few km of all of the high-yield tests contains a continuous record of isotopes, which are of interest (e.g. 14 C, 236 U, 239, 240 Pu) through the testing period. Prior to the present work, 14 C measurements at ∼2-month resolution had shown pronounced peaks in the Δ 14 C data that coincided with the times at which tests were conducted. Here we report measurements of 236 U and 239, 240 Pu on the same coral using accelerator mass spectrometry, and again find prominent peaks in the concentrations of these isotopes that closely follow those in 14 C. Consistent with the 14 C data, the magnitudes of these peaks do not, however, correlate well with the explosive yields of the corresponding tests, indicating that smaller tests probably contributed disproportionately to the debris that fell in the lagoon. Additional information about the different tests can also be obtained from the 236 U/ 239 Pu and 240 Pu/ 239 Pu ratios, which are found to vary dramatically over the testing period. In particular, the first thermonuclear test, Ivy-Mike, has characteristic 236 U/ 239 Pu and 240 Pu/ 239 Pu signatures which are diagnostic of the first arrival of nuclear test material in various archives. Highlights: 236 U and 239, 240 Pu in a Porites Lutea coral on a timescale of months are discussed. The 240 Pu/ 239 Pu and 236 U/ 239 Pu isotopic ratios vary dramatically over time. The Ivy-Mike signal provides an excellent time marker in environmental archives.